Incidental findings on array comparative genomic hybridization: detection of carrier females of dystrophinopathy without any family history. (21st July 2014) - Nguyen, K.; Putoux, A.; Busa, T.; Cordier, M.P.; Sigaudy, S.; Till, M.; Chabrol, B.; Michel‐Calemard, L.; Bernard, R.; Julia, S.; Malzac, P.; Labalme, A.; et al.
Abstract Array comparative genomic hybridization (aCGH) has progressively replaced conventional karyotype in the diagnostic strategy of intellectual disability (ID) and congenital malformations. This technique increases not only the diagnostic rate but also the possibility of finding unexpected variants unrelated to the indication of referral, namely incidental findings. The incidental finding of copy number variants (CNVs) located in X‐linked genes in girls addresses the crucial question of genetic counseling in the family. We report here five cases of CNVs involving the dystrophin gene detected by aCGH in girls referred for developmental delay, without any family history of dystrophinopathy. The rearrangements included three in‐frame deletions; one maternally and two paternally inherited, and two frameshift duplications: one de novo and one from undetermined inheritance. In two cases, the deletion identified in a girl was transmitted by the asymptomatic father. In the case of the maternally inherited deletion, prenatal diagnosis of dystrophinopathy was proposed for an ongoing pregnancy, whereas the cause of developmental delay in the index case remained unknown. Through these cases, we discussed the challenges of genetic counseling in the family, regarding the predictive issues for male individuals at risk for a muscular dystrophy without precise knowledge of the clinical consequences of some CNVs in the DMD gene.